2020
DOI: 10.1002/pd.5874
|View full text |Cite
|
Sign up to set email alerts
|

Biometric assessments of the posterior fossa by fetal MRI: A systematic review

Abstract: Background Posterior fossa abnormalities (PFAs) are commonly identified within routine screening and are a frequent indication for fetal magnetic resonance imaging (MRI). Although biometric measurements of the posterior fossa (PF) are established on fetal ultrasound and MRI, qualitative visual assessments are predominantly used to differentiate PFAs. Objectives This systematic review aimed to assess 2‐dimensional (2D) biometric measurements currently in use for assessing the PF on fetal MRI to delineate differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…In clinical practice, fetal brain MRI biometry is performed on series of two-dimensional (2D) 3-to 4-mm-thick slices acquired in three orthogonal planes by T2-weighted sequences (T2WSs). These T2WS-based measurements are then compared to reference values (4,(12)(13)(14)(15). In two large-scale studies, a good inter-rater agreement on T2WS was found for most brain biometric measurements (4,16).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, fetal brain MRI biometry is performed on series of two-dimensional (2D) 3-to 4-mm-thick slices acquired in three orthogonal planes by T2-weighted sequences (T2WSs). These T2WS-based measurements are then compared to reference values (4,(12)(13)(14)(15). In two large-scale studies, a good inter-rater agreement on T2WS was found for most brain biometric measurements (4,16).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the stability of the BV angle along pregnancy allows its comparison between anomalies without the interference of the gestational age. McKinnon et al ( 14 ) found similarly, that the tegmento-vermian angle measured by MRI remains unchanged with gestational age, whereas measurements of the tentorial angle are correlated with gestational age.…”
Section: Discussionmentioning
confidence: 90%
“…Other measurements have been previously described to objectively assess the PFFC by fetal MRI ( 15 17 ). Mckinnon et al ( 14 ) have reviewed all these measurements in a systematic review published in 2020, identifying those that could be useful in the assessment of PFFC. Despite all the previous publications, we propose two easy and reproducible measurements to calculate the brainstem-tentorium angle, (BT1 and BT2 angles), that could be used, not only in MRI, but also in ultrasound.…”
Section: Discussionmentioning
confidence: 99%